Indirect Photon-Counting Detector with a GAGG Scintillator for Low-Energy Photon Detection - Baek, Cheol-Ha; Lee, Hakjae; Kim, Daehong (International Journal of Engineering and Technology, 2018)
Background/Objectives: The aim of this study was to explore the properties of indirect detection using a scintillator and silicon photomultiplier, as scintillators are highly sensitive for breast cancer detection.Methods/Statistical analysis: Silicon photomultipliers (SiPM) and Cerium-doped Gd3Al2Ga3O12 (GAGG) scintillator crystals were used to fabricate a scintillation detector, and its characteristic of spectroscopy were compared to the results of LYSO and CsI using γ-ray spectroscopic measurement. The resulting energy resolutions of each scintillation detector, comprising a single crystal scintillator (volume size: 3×3×2 mm3) and a SiPM (active area: 3×3 mm2) for a γ-ray source, such as 241Am, were measured and compared.Findings: The 137Cs source yields an energy resolution of 5.23 and 20.31% at 661 keV for the GAGG and LYSO scintillators, respectively. Alternatively, because the CsI scintillator did not yield a distinct energy peak, an energy resolution was not measured. The 241Am source yields an energy resolution of 28.88 and 36.12% at 59.5 keV for the GAGG and LYSO scintillators, respectively. Measured energy peaks of the 241Am source were 62.7 and 64.6 keV for GAGG and LYSO scintillators, respectively. The energy peak of the 241Am source for CsI was not measured because the CsI scintillator did not yield a distinct energy peak of 137Cs source for calibration.Improvements/Applications: The GAGG scintillator could improve the energy resolution of low-energy source than LYSO and CsI scintillators.